2016
DOI: 10.1016/j.jtumed.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Why and how should we measure outcomes in spine surgery?

Abstract: The objectives of spinal surgery for degenerative disorders are to reduce pain and disability and improve patients' quality of life while allowing an early return to work. The incongruence between surgeons' perspectives, findings of imaging exams in terms of fusion statuses or adequate decompression, and patients' satisfaction levels with treatment have underscored the need to evaluate outcomes of spinal surgery with a specific focus on patients' perspectives. Patient-reported outcomes (PRO) are reports on hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 62 publications
0
12
0
2
Order By: Relevance
“…As discussed, functional recovery post spinal procedures is currently reported via proxy parameters such as quality of life, pain and functional scores (VAS, ODI, SF12/SF36, Roland Morris disability index), and duration of hospital stay (8). However, subjective measures alone are strongly influenced by inherent bias and individual variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed, functional recovery post spinal procedures is currently reported via proxy parameters such as quality of life, pain and functional scores (VAS, ODI, SF12/SF36, Roland Morris disability index), and duration of hospital stay (8). However, subjective measures alone are strongly influenced by inherent bias and individual variation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, quantification and comparison of recovery or outcomes in patient's post-spinal procedures used subjective rating scores such as Oswestry Disability Index (ODI), Visual Analogue pain Scale scores (VAS), Short Form Health (SF-12, SF-36) survey scores amongst a variety of others (6)(7)(8). However, the major problem in utilizing these scores is their subjectivity and the inherent bias with self-appraisal, as different individuals perceive and tolerate pain differently (9).…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative spinal disorders have adverse impacts on patients’ quality of life. Because the main objectives of any surgical intervention are to improve health-related quality of life and to reduce disability, instruments capable of measuring patient-oriented outcomes are now increasingly used to evaluate the clinical and functional outcomes from the patients’ perspectives [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many related studies found that ODI Questionnaire has good reliability, validity and responsiveness that is commonly used for clinical practice [10,11] . On the other hand, there are limited studies that convey NCOS as a tool for measuring functional status in patients with lumbar spinal stenosis.…”
Section: Discussionmentioning
confidence: 99%